2016
DOI: 10.17269/cjph.107.5178
|View full text |Cite
|
Sign up to set email alerts
|

Unmet health care needs among sex workers in five census metropolitan areas of Canada

Abstract: OBJECTIVES: This paper examines unmet health care needs in one of Canada's most hard-to-reach populations, adult sex workers, and investigates whether their reasons for not accessing health care are different from those of other Canadians.METHODS: Data gathered in 2012-2013 from sex workers aged 19 and over (n = 209) in five Canadian census metropolitan areas (CMAs) were analyzed to estimate the perceived health, health care access and level of unmet health care needs of sex workers, and their principal reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
(30 reference statements)
5
37
0
Order By: Relevance
“…As reported in our previous analyses (Benoit et al 2016a;Benoit et al 2016b), sex workers in this sample reported higher unmet health care needs (40.4% vs. 14.9% with unmet needs) and have significantly lower levels of confidence in the police (63% vs. 15% report 'not very much' or 'no confidence at all' in the police) compared to other Canadians. This prior research noted that stigma, discrimination and criminalization all likely factored in to these poor outcomes for sex workers.…”
Section: Demographic Profilesupporting
confidence: 75%
See 1 more Smart Citation
“…As reported in our previous analyses (Benoit et al 2016a;Benoit et al 2016b), sex workers in this sample reported higher unmet health care needs (40.4% vs. 14.9% with unmet needs) and have significantly lower levels of confidence in the police (63% vs. 15% report 'not very much' or 'no confidence at all' in the police) compared to other Canadians. This prior research noted that stigma, discrimination and criminalization all likely factored in to these poor outcomes for sex workers.…”
Section: Demographic Profilesupporting
confidence: 75%
“…The same is likely to be the case regarding sex workers' comparatively high unmet healthcare needs. Compared to other Canadians, sex workers in our study were nearly four times more likely to say they had an unmet health need and a quarter recounted judgmental treatment when seeking health care (Benoit et al 2016a). …”
Section: Discussionmentioning
confidence: 64%
“…In the Swiss general population only about 7% of all women receive mental health care (5). Rates of mental health service use among female sex workers in Switzerland are unknown, but international data suggest that unmet health care needs are higher among sex workers than in the general population (6).…”
Section: Introductionmentioning
confidence: 99%
“…Access to health and social services also expanded by informing and providing information about services to the participants’ colleagues, and at times accompanying them to access services [ 17 ]. These outcomes are critically important among populations such as sex workers who, due to the combined effects of stigma and criminalisation, face significant barriers to accessing basic pertinent health knowledge, quality health care, and other public resources [ 48 ].…”
Section: Discussionmentioning
confidence: 99%